Sublingual dermoid cyst: a case report and review of literature - Dutta, Angshuman; Vallur, Srujan; Bothra, Jitendra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Dermoid cysts in the floor of the mouth are relatively uncommon developmental lesions. They generally arise in the midline along the lines of embryonic fusion of the facial processes containing ectodermal tissue. We report a case of 24 year old lady with a Sublingual dermoid cyst which was surgically excised.